UPPER DIGESTIVE ENDOSCOPY IN CAPTIVE COATIS (NASUA NASUA, LINNAEUS, 1766) - Campos, Marina Lazzari de Carvalho [UNESP]; Rahal, Sheila Canevese [UNESP]; Rolim, Luna Scarpari [UNESP]; Mesquita, Luciane Dos Reis [UNESP]; Cassanego, Guilherme Rech [UNESP]; Filadelpho, André Luis [UNESP]; Rech, Vivian Ferreira [UNESP] (American Association of Zoo Veterinarians, 2025)
This study aimed to perform upper digestive endoscopy in clinically healthy coatis (Nasua nasua), based on descriptions in domestic dogs and cats. In addition, research was carried out for Helicobacter in stomach samples. Five adult male coatis, weighing between 2.8 and 4.2 kg, kept in captivity were used. The examination was performed by using a flexible video endoscope with the animals under dissociative anesthesia and positioned in the left lateral decubitus. In general, endoscopic findings among animals were similar. The opening of the upper esophageal sphincter had an oval shape. The esophagus had a pale pink, smooth, and shiny mucosa, with submucosal vessels along its entire length. The contour of the trachea was evident with the impression of a curved appearance on the esophagus wall. Pulsation of the aortic arch was identified in the midthoracic region. The lower esophageal sphincter had an irregular shape resembling a star. In the stomach, rough folds and a mucous membrane with a darker pink color than the esophageal mucosa were observed. The antrum did not have the presence of mucous folds. The pylorus had an oval appearance with peristaltic movements, and the duodenal mucosa had a light pink color. The rapid urease test and histopathologic examination of stomach samples were negative for Helicobacter spp. In conclusion, upper digestive endoscopy of clinically healthy coatis has several similarities with those of domestic dogs and cats, without Helicobacter identification in stomach samples.